Monetary Policy, Foreign Interest Rate impact on Indonesian Bank Credit - Dawood, Taufiq Carnegie (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
This study adds to the economic knowledge by presenting proof based on data for Indonesia, on the consequence to credit provided by domestic banks, due to changes of monetary policy and foreign rates of interest. The subject matter is important for Indonesia because about 88 percent of its overall financing to the private sector in Indonesia are provided by domestic banks through credit channels. Consequently fluctuations of bank credit have significant impact on Indonesia’s financial system’s stability. Applying the Structural VAR method, the current study found that credit channeled by domestic banks in Indonesia are influenced by both rates of interest from abroad and the policy stance of Bank Indonesia. In addition it is found that foreign rates of interest effects bank credit negatively, but turns positive after 12 months. While a monetary contractionary monetary stance by Bank Indonesia decreases the quantity of credit provided by banks. These results underscores the limitation of monetary policy in managing bank credit growth. This results also underlines the need of Bank Indonesia to take into account the impact of foreign interest rates in conducting macro-prudential policies in overseeing credit growth to promote financial stability in Indonesia.